ENED-GEM: A Conceptual Framework Model for Psychological Enjoyment Factors and Learning Mechanisms in Educational Games about the Environment - Fjællingsdal, Kristoffer S.; Klöckner, Christian A. (Frontiers in Psychology, 2017)
Abstract: Based on a thorough review of psychological literature, this article seeks to develop a model of game enjoyment and environmental learning (ENvironmental EDucational Game Enjoyment Model, ENED-GEM) and delineate psychological processes that might facilitate learning and inspire behavioral change from educational games about the environment. A critically acclaimed digital educational game about environmental issues (Fate of the World by Red Redemption / Soothsayer Games) was used as a case study. 249 reviews of the game from the popular gaming and reviewing platform known as Steam were analyzed by means of a thematic content analysis in order to identify key player enjoyment factors believed to be relevant to the process of learning from games, as well as to gain an understanding of positive and negative impressions about the game’s general content. The end results of the thematic analysis were measured up to the suggested ENED-GEM framework. Initial results generally support the main elements of the ENED-GEM, and future research into the importance of these individual core factors is outlined.